Evaluasi Tingkat Pengetahuan Mahasiswa Farmasi Universitas Tadulako Palu Mengenai Obat Golongan Kortikosteroid - Tirza Retno Kinasih Baginda; Amelia Rumi; Yuliet Yuliet (Syntax Corporation Indonesia, 2021)
The knowledge level of pharmacy students about corticosteroid drugs is crucial since corticosteroid drugs have many dangerous side effects. This study aims to determine the knowledge level of the Faculty of Mathematics and Natural Sciences Pharmacy students at Tadulako University Palu regarding corticosteroid drugs and the factors that influence them. The study used a cross-sectional method using a questionnaire to 250 active students of the Faculty of Mathematics and Natural Sciences, Tadulako University Pharmacy study class 2017, 2018, and 2019. The sampling technique is purposive sampling. Descriptive data analysis used the chi-square test. The results showed that the knowledge level of pharmacy students about corticosteroid drugs showed that 36.4% of respondents had good knowledge, 31.6% had enough knowledge, and 32% had insufficient knowledge. The results of statistical tests showed a significant relationship between the knowledge level and age with a batch of pharmacy students (p-value <0.05). The conclusion is that Pharmacy students of the Faculty of Mathematics and Natural Sciences at Tadulako University have good knowledge regarding the dominant corticosteroid drugs and that the age and class of the students affect the knowledge level.